2003
DOI: 10.1023/a:1022153327339
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Size and Response of Locally Advanced Breast Cancers to Neoadjuvant Chemotherapy (Weekly Paclitaxel and Epirubicin) with Serial Enhanced MRI

Abstract: Serial, dynamic, enhanced MRI monitoring of chemotherapeutic response in patients with locally advanced breast cancer can be used to assess early response to chemotherapy and post-chemotherapy tumor size change. Although the residual tumor size on MRI correlated well with the microscopic findings, surgical determination of residual cancer load is still recommended to avoid underestimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
71
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 19 publications
7
71
1
4
Order By: Relevance
“…Other groups have reported correlations of r ¼ 0.6 (Partridge et al, 2002) and r ¼ 0.982 (Cheung et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other groups have reported correlations of r ¼ 0.6 (Partridge et al, 2002) and r ¼ 0.982 (Cheung et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have suggested that MRI is a more accurate method of delineating residual tumour following neoadjuvant chemotherapy than clinical, ultrasound or mammographic assessment (Boetes et al, 1995;Abraham et al, 1996;Drew et al, 1999Drew et al, , 2001Fischer et al, 1999;Balu-Maestro et al, 2002;Rieber et al, 2002;Cheung et al, 2003;Rosen et al, 2003;Martincich et al, 2004;Warren et al, 2004). Chemotherapy-induced fibrosis has been shown to impair the evaluation of tumour by conventional radiological methods and physical examination (Cocconi et al, 1984;Segel et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Recent pilot studies in both MRI and Near-Infrared Spectroscopy (NIR) have shown that more global estimates of cancer, such as water content and vascular volume changes, can be good predictors of response in primary breast cancer [14][15][16][17][18]. Total water content and vascular volume are robust signals in that they can be measured with a good signal to noise ratio, and biological variations in these are generally low, except in response to intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Total water content and vascular volume are robust signals in that they can be measured with a good signal to noise ratio, and biological variations in these are generally low, except in response to intervention. Further, and of great potential interest, in pilot studies there is evidence that these biophysical changes occur within the first cycle of chemotherapy [14][15][16][17][18], which could have considerable prognostic value if confirmed with high specificity. Thus a key factor being tested in multi-center trials now is to determine the sensitivity and specificity of NIR or MRI as a measurement of response within the first cycle of NACT, and if this value is sufficient for a cost-effective test.…”
Section: Introductionmentioning
confidence: 99%
“…Promising results have been reported for diagnosis (7), therapy response monitoring (8,9), and survival prediction (10)(11)(12). Both semiquantitative (calculated directly from the contrast uptake curves) and pharmacokinetic parameters (based on kinetic modeling of the contrast uptake curves) (13) can be obtained by analyzing MRI data from the breast.…”
mentioning
confidence: 99%